2019
DOI: 10.1002/brb3.1236
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported navigation ability is associated with optic flow‐sensitive regions’ functional connectivity patterns during visual path integration

Abstract: Introduction Spatial navigation is a complex cognitive skill that varies between individuals, and the mechanisms underlying this variability are not clear. Studying simpler components of spatial navigation may help illuminate factors that contribute to variation in this complex skill; path integration is one such component. Optic flow provides self‐motion information while moving through an environment and is sufficient for path integration. This study aims to investigate whether self‐reported navigation abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…In a free-behavior context, vestibular inputsincluding translational and rotational signals and their interactions with vision-may exert strong impacts on the path integration process. The present paradigm may have restrictions similar to those used in human studies using functional magnetic resonance imaging, which investigate the role of optic flow on navigational behavior in a VR setup [33][34][35]. Previous human studies have shown that the hippocampus and RSC work in concert for successful path integration [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…In a free-behavior context, vestibular inputsincluding translational and rotational signals and their interactions with vision-may exert strong impacts on the path integration process. The present paradigm may have restrictions similar to those used in human studies using functional magnetic resonance imaging, which investigate the role of optic flow on navigational behavior in a VR setup [33][34][35]. Previous human studies have shown that the hippocampus and RSC work in concert for successful path integration [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…The multiple regression analyses showed that this network spanned posterior structures linked to visuospatial processing. Activation of the left superior occipital gyrus was reported which corresponds to visual area V3A and which is involved in optic flow tracking for visual path integration (Sherrill et al, 2015 ; Zajac et al, 2019 ). Also, our landmark-based navigation paradigm elicited activity in the ventral temporal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…This network spanned posterior structures linked to visuo-spatial processing. We reported activation of the left superior occipital gyrus which corresponds to visual area V3A and is involved in optic flow tracking for visual path integration (Sherrill et al, 2015; Zajac et al, 2019). In addition, our landmark-based navigation paradigm elicited activity in the ventral temporal cortex.…”
Section: Discussionmentioning
confidence: 99%